2012
DOI: 10.1002/iub.567
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the role of cysteine and methionine residues in the antioxidant activity of human serum albumin using recombinant mutants

Abstract: SummaryThe importance of cysteine (Cys) and methionine (Met) residues for the antioxidant activity of human serum albumin (HSA) was investigated using recombinant HSA mutants, in which Cys34 and/or the six Met residues had been mutated to Ala. The scavenging activities of the mutants against five reactive oxygen and nitrogen species were evaluated by a chemiluminescence assay, electron paramagnetic resonance spectroscopy, or a HPLC-flow reactor assay. Our results showed that the contributions of Cys34 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…3). This finding is in accordance with that of Iwao et al [19], who registered only 40% activity of the recombinant mutant C34A. If the free Cys residue was placed in another position in HSA, then it could probably also have an antioxidant effect; however, its new molecular environment could affect its antioxidant effect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…3). This finding is in accordance with that of Iwao et al [19], who registered only 40% activity of the recombinant mutant C34A. If the free Cys residue was placed in another position in HSA, then it could probably also have an antioxidant effect; however, its new molecular environment could affect its antioxidant effect.…”
Section: Discussionsupporting
confidence: 92%
“…HSA has six Met residues (Fig. 1), and a previous study from our laboratory revealed that mutating all six Mets to alanines resulted in diminished antioxidant activity against H 2 O 2 and four other types of ROS [19]. The investigation also revealed that Cys34 plays a more important role than the other Met residues for the antioxidant activities of HSA.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It also influences fluid distribution of tissues providing 75% of the intravascular oncotic pressure (Doweiko and Nompleggi, 1991). Additional functions include a role in acid-base physiology owing to its 16 histidine imidazole residues (Agrafiotis et al, 2014;Watson, 1999), anti-oxidant properties by neutralising oxygen radicals (Anraku et al, 2013;Bruschi et al, 2013;Iwao et al, 2012), anticoagulation properties (Galanakis, 1992;Stoffersen, 1979, 1980), and the binding and transport of ligands (Anand and Mukherjee, 2013;Dalvit et al, 2002;Sarver et al, 2005).…”
Section: Albuminmentioning
confidence: 99%